Endovascular treatment for Angio-Seal-related complications: long-term outcome. Issue 4 (April 2016) - Ganai, B.; Pennycooke, K.; Given, M.F.; Keeling, A.; Moneley, D.; Lee, M.J.
Highlights: Endovascular techniques can be used to treat Angio-Seal vascular closure device related stenotic, occlusive and embolic complications. A range of techniques can be employed including thrombolysis, angioplasty and stent placement. This can avoid surgery, particularly in medically unfit patients.